Novel Imidazo[2,1-b]oxazole Derivatives Inhibit Epithelial Cell Transformation and Triple Negative Breast Cancer Tumorigenesis - Bhattarai, Poshan Yugal; Oh, Chang-Hyun; Kim, Garam; Kim, Min Soo; Lee, Bong Sang; Choi, Hong Seok (INT INST ANTICANCER RESEARCH, 2020)
Background/Aim: Triple negative breast cancer (TNBC) is an aggressive type of breast cancer with limited targets for chemotherapy. This study evaluated the inhibitory effects of novel imidazo[2,1-b]oxazole-based rapidly accelerated fibrosarcoma (RAF) inhibitors, KIS719215-1 and KISI19215-2, on epithelial cell transformation and TNBC tumorigenesis. Materials and Methods: Immunoblotting, BrdU incorporation assay, reporter gene assay, and soft agar assay analyses were performed. In vivo effects were studied using the BALB/c mouse xenograft model. Results: KIS719215-1 and KIS719215-2 inhibited the RAFs-MEK1/2-ERK1/2 signalling pathway induced by EGF in MDA-MB-231 cells, which inhibited c-fos transcriptional activity and activator protein-1 transactivation activity. KIST0215-1 and KIS70215-2 also prevented neoplastic transformation of .1B6 CI41 mouse epidermal cells induced by EGF and consistently suppressed the growth of tumours formed by 4TI cells in BALB/c mice. Conclusion: Inhibition of RAF kinases using KIST0215-1 and KIST0215-2 is a promising chemotherapeutic strategy to treat TNBC.